Study of projectile fragmentation reaction with isochronous mass spectrometry. (26th November 2015) - Tu, X L; Mei, B; Zhang, Y H; Xu, H S; Litvinov, Yu A; Huang, W J; Podolyak, Z; Kelic-Heil, A; Zhang, W; Litvinov, S A; Blaum, K; Zhou, X H; et al.
Abstract: Relative yields of fragments following the 78 Kr projectile fragmentation in a beryllium target were measured in a storage ring by using isochronous mass spectrometry (IMS). Odd–even staggering of the relative fragment yields is observed and can be explained by the odd–even staggering of the particle-emission threshold energies. IMS is a complementary technique to γ -ray spectroscopy for measuring isomeric ratios, in particular for nuclides with long lifetimes. It was found that the isomeric yield ratios in 53 Fe are almost constant for different longitudinal momenta.